Topoclimatología de la cuenca del Río Mapocho - Romero, Hugo; Vinagre, José (Investigaciones Geográficas: Una mirada desde el sur, 1985)
Particular geographic morphology of the country is responsible by the great climatic especificity of Central Chile basins, such as Santiago, where orographic and the dynamic of the atmosphere relationship, regulates the distribution of climate elements, !.e. mean temperatures, rainfall, relative humidity, winds, solar radiation, evapotranspiration and the lenght of vegetative development. Using annual long term averages, regression lines have been calculated between climatic data and some causal factors, selected according to a trend surface analysis. So, regression coefficients express relative weight of height, distance to Maipo valley and distance to main contour lines. From those equations isa-rithmic maps have being drawing and from their overla ying, five climatic areas are distinguished: Leeward of coastal mountain chain; Windward of the Andes chain, piedmont and hight andes valleys; Continental central sector; an area under maritime influence inland Maipo Valley and the N. W. sector. Residuals of estimate values are particularly lows in temperatures and rainfall. Coastal and Andes mountain landscapes present two thermal gradients, one positive below inversion layer and one negative, above this layer: at the piedmont, temperature increases since 15 to 17•‹C between 700 and 1.000 m and there, decreases to g•‹C at 2.000 height. The main climatic difference between both slopes is the coastal rainshadow effect which decreases rainfall from 600 mm at windward to 300 mm at leeward and the Andes windward rainshooter effect wich increases yearly precipitation since 450 mm at 900 m to 850 mm at2.000 m. This last area, because seasonality of rainfall, strong South winds blowing above 1.000 m height, IOW relative humidity (annual mean is 50%) and the presence of the PC isotherm, explains the arid environment lasting most of the year (mean annual ETP is between 110 and 155 mm). The most continental areas are located at the Central section of the basin and its extension towards N. W. In both cases the extreme orographic confinement determines a steady air, with large thermal oscilation, resultlng from high mean maximun values (over 3PC) in summer and mean minimum under 3OC in winter. The last area is under oceanic influences throught Maipo Valley, with minimun temperatures over5OC and maximals between 0,5 and 1,F C lower, both respect to the rest of the basin. Rainfall is, on the other hand, 125 mm in annual average larger and, as a consequence, allows minors values in ETP and vegetative development. In al1 the basin, solar exposition and rainfall are variables and, therefore ETP. A large amount of small and big valleys control the behaviour of local winds, changing regular climatic patterns.